Modeled timing of flooding for the Beringian shelf for the past 20,000 years - Matthias Fuchs; Miriam C Jones; Evan J Gowan; Steve Frolking; Katey M Walter Anthony; Guido Grosse; Benjamin M Jones; Jonathan O extquotesingleDonnel; Laura Susan Brosius; Claire C Treat (PANGAEA, 2024)
The paleo bathymetry grids (PaleoMIST 1.0 (Gowan et al. 2021) were used to calculate the timing of flooding in the Beringia study region. The resulting GeoTiff (Year of flooding.tif) has a spatial resolution of 5,000 m and each pixel contains the modeled time of flooding (in yrs BP), e.g., when this location was flooded by rising sea levels. PaleoMIST 1.0 is a glacial isostatic adjustment-based paleo topographic reconstruction model that includes relative sea level and paleo bathymetry as an output. The model was created to estimate the sea level contribution of the global ice sheets and is validated using observations of relative sea level change. To estimate the timing of flooding, nine of the PaleoMIST 1.0 raster data sets (20,000 yrs BP to 0 yrs BP, with 2,500 years time steps) were used. In order to estimate the timing of flooding for each pixel, we first calculated the linear increase (or decrease) for each pixel between two sequential PaleoMIST 1.0 grids to establish grids for every 1,000 years. In addition, we calculated the timing of flooding for each pixel, again by assuming a linear transition between two sequential grids. The timing of flooding was then determined as the point in time when a pixel elevation value relative to sea level switched from positive (>0; above sea level) to negative (<0; below sea level). These two procedures allowed us to estimate the area, which became flooded in each 1,000-year time interval from 20,000 yrs BP to present (0 yrs BP). The associated files can be imported, read and viewed with a geographic information system software or through a programming language.